Physics Teaching: Development of Lectora Inspire with Multiple-Representation Approach to Reduce Of Misconception - Khairunnisa Khairunnisa; Ishafit Ishafit; Suritno Fayanto (Jurnal Dedikasi Pendidikan, 2020)
This study aims to determine the validity of the development of multimedia learning physics with a multiple-representation approach to reduce misconceptions on the material momentum and impulses This research is a development study with ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. This research using descriptive analysis techniques, i.e., with the yield on the validity of multimedia learning by using instruments of validation, Multimedia learning has been through a phase test validity by subject matter experts with an average percentage of 95.83% with very valid criteria, a media expert at 82.64% with very valid, and learning experts of 81.25% with a very valid, so that multimedia teaching physics with multiple representations valid approach used as a medium of learning in the classroom.